x+(x+2)=-67

Simple and best practice solution for x+(x+2)=-67 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+(x+2)=-67 equation:


Simplifying
x + (x + 2) = -67

Reorder the terms:
x + (2 + x) = -67

Remove parenthesis around (2 + x)
x + 2 + x = -67

Reorder the terms:
2 + x + x = -67

Combine like terms: x + x = 2x
2 + 2x = -67

Solving
2 + 2x = -67

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 2x = -67 + -2

Combine like terms: 2 + -2 = 0
0 + 2x = -67 + -2
2x = -67 + -2

Combine like terms: -67 + -2 = -69
2x = -69

Divide each side by '2'.
x = -34.5

Simplifying
x = -34.5

See similar equations:

| log^4[log^4(2x)]=1 | | 0=x^2+26+48 | | log(x)+log(x+5)=log(6x+12) | | 17.625=-2(c+15) | | -5x+6-(7-3x+2x+4)=3 | | 3.67(12-a)=43 | | 3x-5=5x-11 | | x+9=55 | | 12-(4-3x)=21-(12+7x) | | x+7=69 | | y+8=-25 | | 16-(3x+20)=(17-2x)-15 | | 18x-9=9x+3 | | 4p+3g=395 | | -(8-2x)=32 | | 7+25x=20x+10 | | X*0.05=6 | | -(8x-2x)=32 | | 3(x+2)+2x=2(x-7)+2x+5 | | 12y-32=-15 | | 82-(-3)= | | 12y-32=-35 | | -21-(-24)= | | x-24=2x+5 | | 8n^2=24n | | 6x+9=-72-6x | | 24*6x=9-9x | | n^2+w=12 | | x-3.75=12.25 | | z=2x-7y | | 6(x+31)=216 | | 1/3p=12 |

Equations solver categories